2010
DOI: 10.1097/tp.0b013e3181c6ff8d
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Inhibitor-Based Primary Therapy for Antibody-Mediated Renal Allograft Rejection

Abstract: Proteasome inhibitor-based combination therapy provides a potential means for rapid DSA elimination in early acute AMR in renal transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
171
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(177 citation statements)
references
References 19 publications
(27 reference statements)
5
171
0
1
Order By: Relevance
“…In the context of AMR, PI seems to reduce the titers of immunodominant DSAs by 50%, especially in early AMR. 102 A similar but transient reduction rate has also been observed for preformed anti-HLA antibodies in a prospective trial of PI-based desensitization. 103 Interestingly, Woodle et al 103 also reported a low rate of dnDSA formation (12.5%) in patients who were desensitized.…”
Section: The Effect Of B or Plasma Cell-targeted Therapy On Dsasmentioning
confidence: 59%
“…In the context of AMR, PI seems to reduce the titers of immunodominant DSAs by 50%, especially in early AMR. 102 A similar but transient reduction rate has also been observed for preformed anti-HLA antibodies in a prospective trial of PI-based desensitization. 103 Interestingly, Woodle et al 103 also reported a low rate of dnDSA formation (12.5%) in patients who were desensitized.…”
Section: The Effect Of B or Plasma Cell-targeted Therapy On Dsasmentioning
confidence: 59%
“…20 In addition, bortezomib has received recent attention in studies showing that it directly eliminates Ab-producing plasma cells and thus prevents Ab-mediated graft rejection after renal transplantation. [21][22][23] Moreover, improvement of platelet transfusion refractoriness was observed in a patient with HLA class I antibodies with the treatment of bortezomib for multiple myeloma. 24 The effectiveness of high-dose i.v.…”
Section: Discussionmentioning
confidence: 99%
“…This agent is now being used to attempt reduction of DSA in sensitized patients [92,93]. While many centers have incorporated this agent into treatment of AMR [94][95][96], its use for immunomodulation is limited to case reports. There have been 2 case reports that examined the use of bortezomib as a desensitizing agent pre-transplant.…”
Section: Future Of Crossmatch Incompatible Donorsmentioning
confidence: 99%